Military Ethics Education – What Is It, How Should It Be Done, and Why Is It Important? - Whetham, David (Conatus - Journal of Philosophy, 2023)
This paper explores the topic of military ethics, what we mean by that term, what it covers, how it is understood, and how it is taught. It suggests that the unifying factor that makes this a coherent subject beyond individual national interpretations of it is the core idea of military professionalism. The paper draws out the distinction between training and education and draws on research conducted by a number of different people and agencies, including the International Committee of the Red Cross, to establish what factors contribute to effective pedagogy and the inculcation of appropriate attitudes and behaviours. The paper concludes by looking at the way military ethics contributes to military outcomes from protecting civilians and the vulnerable to building resilience in our own military personnel to protect their mental health, through to the strategic costs of losing the moral high ground if behaviour is seen to fall short of that expected from military professionals.